THE LAND USE PRIORITY RANKING WITH THE APPROACH OF ANALYTIC HIERARCHY PROCESS (AHP) ON THE BOUNDARY OF ENTIKONG - Robby Irsan; Luthfi Muta'ali; S Sudrajat (Department of Geography Education, University of Jember, 2018)
Entikong is a sub-districts located in the borderline, northern end of Sanggau Regency directly adjacent to Sarawak, Malaysia. The growth of Entikong as a center of growth does not provide a downward trickle effect, but it creates an excessive resources exploitation effect to the surrounding area (backwash effect). The land use within an area should be adjusted to its function. For that reason, this research will determine the priority and rank of land use by using the Analytic Hierarchy Process (AHP). The ranking is based on four aspects of criteria; social, economic, institutional, and environmental. The hierarchy model is sorted into alternatives, criteria, and sub-criteria. The criteria and subcriteria are compared, as well as the value of consistency. After data processing and analyzing with Expert Choice software version 11, the researcher found that the main priority of land use in Entikong is for plantation, which is 29,7%. Keywords: AHP, Land Use, Expert Choice References Adimihardja, A. (2006). Strategi mempertahankan multifungsi pertanian di indonesia. Jurnal Litbang Pertanian. Bourgeois, R., Penunia, E., Bisht, S., & Boruk, D. (2017). Foresight for all: Co-elaborative scenario building and empowerment. Technological Forecasting and Social Change. https://doi.org/10.1016/j.techfore.2017.04.018 Ernan Rustiadi, Sunsus Saefulhakim, D. R. P. (2011). Perencanaan dan Pengembangan Wilayah. Restpent Press. Fandelli, C. (2014). Bisnis Konservasi Pendekatan Baru Dalam Pengelolaan Sumberdaya Alam dan Lingkungan Hidup (2nd ed.). Yogyakarta: Gadjah Mada University Press. Retrieved from http://ugmpress.ugm.ac.id/id/product/sains-teknologi/bisnis-konservasi-pendekatan-baru-dalam-pengelolaan-sumberdaya-alam-dan-lingkungan-hidup Giyarsih, S. R. (2010). POLA SPASIAL TRANSFORMASI WILAYAH DI KORIDOR YOGYAKARTA-SURAKARTA Spatial Pattern of Regional Transformation In Yogyakarta-Surakarta Corridor. Forum Geografi. Hidayat, W., Rustiadi, E., & Kartodihardjo, H. (2015). Dampak Pertambangan Terhadap Perubahan Penggunaan Lahan dan Kesesuaian Peruntukan Ruang (Studi Kasus Kabupaten Luwu Timur, Provinsi Sulawesi Selatan). Jurnal Perencanaan Wilayah Dan Kota. https://doi.org/10.5614/jpwk.2015.26.2.5 IPCC. (2000). Land Use, Land-Use Change, and Forestry. Forestry. https://doi.org/DOI: 10.2277/0521800838 Ishartono & Raharjo, S. T. (2015). Sustainable Development Goals (SDGs) Dan Pengentasan Kemiskinan. Social Work Jurnal. https://doi.org/ttps://doi.org/10.24198/share.v6i2.13198 Prawira, N. G. A., & Ariastita, P. G. (2014). Rumusan Insentif dan Disinsentif Pengendalian Konversi Lahan Pertanian di Kabupaten Gianyar. Jurnal Teknik Pomits. Saaty, T. L. (2008). Decision making with the analytic hierarchy process. International Journal of Services Sciences. https://doi.org/10.1504/IJSSCI.2008.017590 Copyright (c) 2018 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License